13C CP/MAS NMR studies on the curing characteristics of phenol formaldehyde resin in the presence of nano cupric oxide and surfactants. Issue 1 (23rd August 2013) - Gao, Wei; Du, Guanben
<x xml:space="preserve">Abstract</x> The effect of nano cupric oxide (CuO) in combination with surfactants on the curing characteristics of phenol formaldehyde (PF) resin analyzed using solid 13C CP/MAS NMR, including the bonding strength of plywood prepared by modified resin, was investigated in this study. The results showed that nano CuO alone improved the cure of PF resin. The intensity of the functional groups of the PF mixture was maintained during the curing process as sodium lignosulfonate was simultaneously introduced. Furthermore, nano CuO and alkane surfactant together modified the PF resin conformation. The shear strength of the plywood showed that the addition of nano CuO (1%) alone or in combination with alkane surfactant (0.55%) or sodium lignosulfonate (0.55%) to the PF resin mixture was effective. And this approach met the important criteria for its application in the manufacture of plywood. POLYM. COMPOS., 35:113–117, 2014. © 2013 Society of Plastics Engineers